2023
DOI: 10.1071/wr22093
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing shows south-east Queensland koalas (Phascolarctos cinereus) prefer areas of higher tree canopy height within their home ranges

Abstract: Context. Home range studies allow investigation of faunal habitat use within a well-defined area, and for some species, the concept of 'core' and 'non-core' home ranges provides the means to examine how resource use varies within home ranges. Taking this approach, we investigated whether koalas preferentially used areas of taller forest canopy within home ranges. After an extensive examination of data quality and home range estimation methods, we used remote sensing techniques to provide canopy height informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 70 publications
4
2
1
Order By: Relevance
“…Our results differ from those of a recent study that also assessed tree use by koalas using GPS‐tracking data and a canopy height model (Mitchell et al., 2023). Koala core home ranges in the peri‐urban landscapes of south‐east Queensland were comprised of a significantly higher proportion of the highest height class (28 m median) than non‐core areas, highlighting regular use of areas with higher canopies in this landscape.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our results differ from those of a recent study that also assessed tree use by koalas using GPS‐tracking data and a canopy height model (Mitchell et al., 2023). Koala core home ranges in the peri‐urban landscapes of south‐east Queensland were comprised of a significantly higher proportion of the highest height class (28 m median) than non‐core areas, highlighting regular use of areas with higher canopies in this landscape.…”
Section: Discussioncontrasting
confidence: 99%
“…Core areas in our study represented 23%–29% of 95% AKDE home ranges, which is similar to that found by Mitchell et al. (2023) in south‐east Queensland.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations